Respostas

  • Usuário do Brainly
2014-09-03T16:50:44-03:00
x^3+6x^2+8x=0

vamos colocar x em evidência

x(x^2+6x+8)=0

x=0

 x^{2} +6x+8=0
Δ=b²-4ac
Δ=36-32
Δ=4

x= \frac{-b\pm \sqrt{\triangle} }{2a}

x= \frac{-6\pm \sqrt{4} }{2}

x'= \frac{-6+2}{2}=- \frac{4}{2} =-2

x"= \frac{-6-2}{2} =- \frac{8}{2} =-4

\fbox{$S={-4,-2,0}$}

b)
-2 x^{2} -4x+6=0

vamos( ÷-2)

 x^{2} +2x-3=0

Δ=b²-4ac
Δ=4+12
Δ=16

x= \frac{-b\pm \sqrt{\triangle} }{2a}

x= \frac{-2\pm \sqrt{16} }{2}

x'= \frac{-2+4}{2} = \frac{4}{2} =2

x"= \frac{-2-4}{2} =- \frac{6}{2} =-3

S={-3,1}